Superior semicircular canal dehiscence syndrome: Two cases report. - Guimarães, Joana (2011)
The Superior Semicircular Canal Dehiscence Syndrome (SSCDS) has been characterized by vestibular symptoms induced by loud sound (Tullio phenomenon) or stimuli that change middle ear or intracranial pressure, and conductive hearing loss. The autors present the case report of 2 female patients:• 44 years-old, referring left hearing loss and tinnitus with vertigo; the observation revealed bilateral conductive hearing loss with a left larger air-bone gap in low frequencies and type A tympanogram with normal acoustic stapedial reflex; the vestibular evoked myogenic potential (VEMP) and computed tomography (CT) confirmed superior semicircular canal dehiscence. The patient was submitted to surgery to repair the bone dehiscence. One month after surgery, she presented vestibular symptoms improvement;• 57 years-old, who presents vertigo and chronic dysequilibrium complaints, with no hearing loss; the observation revealed normal audiometry and normal impedance, the videonystagmography showed right hyporeflexia and electrococleography had no labyrinthine hydrops criteria; VEMP and CT confirmed superior semicircular canal dehiscence.